Interferon alpha inducible protein 6 is a negative regulator of innate immune responses by modulating RIG-I activation - Villamayor, Laura; Rivero, Vanessa; López-García, Darío; Topham, David J.; Martínez-Sobrido, Luis; Nogales, Aitor; DeDiego, Marta L. (Frontiers in Immunology, 2023)
Innate immune responses mediated by interferons (IFNs), IFN-stimulated genes (ISGs), and inflammatory cytokines are essential to establish an antiviral response. As such, retinoic acid-inducible gene I (RIG-I) is a key sensor of virus infections, mediating the transcriptional induction of IFNs and inflammatory proteins. However, these responses need to be highly regulated since exacerbated responses could be detrimental to the host. In this work, we show, for the first time, that knocking-down or knocking-out the expression of IFN alpha-inducible protein 6 (IFI6) increases IFN, ISG, and pro-inflammatory cytokine expression after Influenza A Virus (IAV), Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), and Sendai Virus (SeV) infections, or poly(I:C) transfection. We also describe how overexpression of IFI6 produces the contrary effect, even in vivo, indicating that IFI6 negatively modulates the induction of innate immune responses. Knocking-down or knocking-out the expression of IFI6 decreases the production of infectious IAV and SARS-CoV-2, most likely through its effect on antiviral responses. Remarkably, we report a novel interaction of IFI6 with RIG-I, most likely mediated through binding to RNA, that affects RIG-I activation, providing a molecular mechanism for the effect of IFI6 on modulating innate immunity. Importantly, these new functions of IFI6 could be exploited to treat diseases associated with excessive induction of innate immune responses and to broadly combat viral infections, including IAV and SARS-CoV-2.